PENGARUH SISTEM PENGUPAHAN TERHADAP TINGKAT KEPUASAN KARYAWAN PT. BENGKULU SAWIT LESTARI - Evoni Anselia; Wahyu Setya Ratri; Nanang Kusuma Mawardi (Fakultas Pertanian UST, 2023)
Employees want a pay system that they perceive as fair and in line with their expectations. When wages are seen as fair based on job demands, individual skill levels, and community pay standards, satisfaction is likely to result. The purpose of this study is to determine the existing wage system at PT. Bengkulu Sawit Lestari and to find out the effect of the Wage System on the Satisfaction Level of Employees of PT. Bengkulu Sustainable Palm Oil. This research is quantitative research. The population in this study were employees with a total of 150 people consisting of mill managers, staff and employees of PT. Bengkulu Sustainable Palm Oil. Based on the results of calculations from the existing population, the number of samples obtained is 60 samples taken using the slovin husein umar formula. Sampling was done by random sampling. Data were collected using a questionnaire. Data were analyzed using simple linear regression analysis using the research model Y = + X₁ + e. Where Y is employee satisfaction, is the regression coefficient, X₁ is the wage system, and e is the error term. The t count value is 16,204 and the t table value is 2,004. t count > t table, the wage system variable is rejected and the employee satisfaction level variable is accepted, which means that the wage system affects the level of employee satisfaction. From the results of data analysis, it can be concluded that there is a significant influence between the variable wage system on the variable level of employee satisfaction. These results indicate that the wage system is an important thing to be considered by PT. Bengkulu Sustainable Palm Oil. The conclusion is that the wage system has an effect on employee satisfaction. this will have implications for the achievement of the company's vision and mission. Suggestions pay more attention to the selection and determination and acceptance of employees.